FABRICATION OF DENSE FORSTERITE-ENSTATITE POLYCRYSTALS FOR EXPERIMENTAL STUDIES - McDonnell R.D.; Spiers C.J.; Peach C.J. (My University, 2002)
A practical and reliable method for the preparation of fine-grained forsterite and forsterite-enstatite polycrystals, in the system MgO-SiO2s described. The method employs state-of-the-art techniques from materials science, namely sol-gel synthesis, powder processing and sintering. The resulting dense polycrystalline materials are homogeneously fine-grained (1-2 μm) and uniformly foam-textured. Moreover, they are highly reproducible in composition and microstructure. The enstatite content can be controlled to within ~1%, in the range 0-50%, and densities up to 98% of theoretical density can be achieved. The method thus yields polycrystalline forsterite-enstatite material suitable for a range of geochemical, petrological and geophysical studies.
Keywords: OLIVINE; PYROXENE; SINTERING; SOL-GEL; SYNTHESIS